Pengaruh Disiplin kerja, Motivasi dan Komitmen Organisasi Terhadap Kinerja Pegawai Dinas Pemberdayaan Perempuan, Perlindungan anak, Pengendalian Penduduk dan Keluarga Berencana (DP3A P2KB) Kota Batu - Khairul Imamul; Rois Arifin; Afi Rachmat Slamet (E-JRM : Elektronik Jurnal Riset Manajemen, 2017)
Abstract               The purpose of this research is to know and analyze the influence of Work discipline, Motivation and Organizational Commitment to Performance of Employees at Department of Women Empowerment, Child Protection, Population Control and Family Planning (DP3A P2KB) Batu City. Population in Research All employees working in the Department of Women's Empowerment, Child Protection, Population Control and Family Planning (DP3A P2KB) Batu City. The sample used is the Office of Women Empowerment, Child Protection, Population Control and Family Planning (DP3A P2KB) Batu City. As for Sampling Technique that if less than 100 better taken all so this research is census research.               Based on the results of this study it is known that the independent variables simultaneously affect Significantly to the bound variable is known value Fhitung 25,426 with the value of sig 0,000 <0,05 then H1 di terimah, meaning the variable discipline work, motivation and Commitment Organization simultaneously affect on Employee Performance. As well as work discipline variables, it is known that THTI value 8,725 with sig value 0.000, <0,05 means partially effect on the performance of employees. The variable of motivation is known value of Thitung 527 with value of sig 0,601> 0,05 meaning that motivation variable do not influence partially to employee performance. Organizational Commitment Variables known Thitung value -320 with sig value 0.750> 0.05 means Organizational Commitment variable does not partially effect on employee performance Keyword : Work discipline, Motivation, Organizational Commitment, and Performance Employees